Paleomagnetic data (inclination, declination, relative paleointensity) in sediment core AMD1902-10GC from Petermann Fjord (Nares Strait, Northern Greenland) - Juliette Girard; Brendan T Reilly; Guillaume St-Onge; France Lagroix; Jean-Carlos Montero-Serrano; Joseph S Stoner; Anne E Jennings (PANGAEA, 2025)
This dataset contains paleomagnetic data (inclination, declination, relative paleointensity) of core AMD1902-10GC. This core was collected in Petermann Fjord (Nares Strait, Greenland, Arctic) during Leg 2 of the 2019 ArcticNet Expedition on board the CCGS Amundsen. Continuous paleomagnetic data were acquired using a 2G Enterprises 755SRM-1.65 cryogenic magnetometer at ISMER. The data obtained for this core were then stacked with 3 other cores from a previous publication to build the Petermann stack (inclination, declination, relative paleointensity), see doi:10.1594/PANGAEA.971851.